A review of the effects of pharmaceutical pollutants on humans and aquatic ecosystem - Jaya Vinny Eapen; Sweety Thomas; Shelmi Antony; Paul George; Jayesh Antony (Exploration of Drug Science)
The presence of high-quality water is essential not only for human survival but also for the well-being of plants and animals. This research aimed to examine studies investigating the occurrence of antibiotics, endocrine disruptors, and other pharmaceutical products in water, sediments, and organisms within aquatic ecosystems. These substances have been linked to numerous adverse health effects on both humans and aquatic life, including reproductive issues and neurotoxic effects. The pervasive utilization of antibiotics in medical and agricultural domains has precipitated their ascension as formidable environmental contaminants. Effluents discharged from pharmaceutical industries constitute significant contributors to aquatic ecosystems’ contamination with antibiotics. These pharmacological agents permeate diverse environmental niches, spanning groundwater, surface water, soils, and wastewater treatment facilities, exhibiting concentrations ranging from nanograms to grams per liter. Concurrently, the indiscriminate and excessive application of antibiotics worldwide has engendered escalating apprehensions pertaining to antimicrobial resistance—a formidable global health exigency. This review also delves into the impact of pharmaceutical pollutants on aquatic environments, particularly as endocrine-disrupting compounds. Analysis of surface water in River Taff and River Ely reveals a consistent discharge of approximately 6 kilograms of pharmaceuticals per day. The study examines particular pharmaceuticals, such as diethylstilbestrol (DES), chlorotriazines, chloroquine, and antineoplastic drugs, elucidating their varied effects on reproductive cycles. Pharmaceutical pollutants in aquatic ecosystems, originating from sources like wastewater, agriculture, and improper disposal, persist and adversely affect organisms through bioaccumulation and biomagnification. These contaminants pose significant ecological and health risks, necessitating effective mitigation strategies.